A liquid chromatography‐tandem mass spectrometry‐based targeted proteomics approach for the assessment of transferrin receptor levels in breast cancer. Issue 10 (25th June 2014) - Yang, Ting; Xu, Feifei; Zhao, Yi; Wang, Shui; Yang, Mi; Chen, Yun; Bendixen, E.
<x xml:space="preserve">Abstract</x> Purpose Overexpression of human transferrin receptor (TfR) has been described qualitatively in various cancers, including breast cancer. Since TfR is also expressed to some extent under normal physiological conditions, increase of specificity and reproducibility in TfR quantification could improve the early detection and prognostic evaluation of cancers. Experimental design A LC‐MS/MS‐based targeted proteomics assay was developed for the determination of TfR in human breast cells and tissue samples. Results We selected the tryptic peptide 681VEYHFLSPYVSPK693 as the surrogate peptide for quantification and used a stable isotope‐labeled synthetic peptide with this sequence as an internal standard. Quality control data indicated acceptable accuracy and precision. Finally, this assay was successfully applied to the quantitative analysis of TfR in three breast cell lines and 36 matched pairs of breast tissue samples. The experimental values were compared with those obtained from conventional analytical methods, including immunofluorescence microscopy, Western blotting, flow cytometry, and immunohistochemistry. Conclusions and clinical relevance Not only is the LC‐MS/MS‐based targeted proteomics assay a more accurate method for the determination of TfR levels, but may afford more reliable quantification of TfR at low concentrations in clinical practice.